Balearic archipelago: three islands, three beta‐thalassemia population patterns. (22nd March 2012) - López‐Escribano, H; Parera, MM; Guix, P; Serra, JM; Gutierrez, A; Balsells, D; Oliva‐Berini, E; Castro, JA; Ramon, MM; Picornell, A
<x xml:space="preserve">Abstract</x> López‐Escribano H, Parera MM, Guix P, Serra JM, Gutierrez A, Balsells D, Oliva‐Berini E, Castro JA, Ramon MM, Picornell A. Balearic archipelago: three islands, three beta‐thalassemia population patterns. The mutation spectrum of 175 β‐thalassemia (β‐thal) carriers, identified in pilot carrier screening on 22, 713 individuals from Balearic Islands (Spain), is reported. The β0 CD39 (C>T) mutation is the most frequent (61.1%), followed by β+ IVS‐I‐110 (G>A) (12.0%), β+ IVS‐I‐6 (T>C) and β0 IVS‐1‐1 (G>A) (3.4% both) and eight other rare mutations (2.9–0.6%); with a distinct prevalence and distribution between islands. Minorca shows the highest prevalence in Iberian populations, with a single mutation, CD39 (C>T), present in most β‐thal carriers. Ibiza is the only Western Mediterranean population where the most frequent β‐thal mutation is IVS‐I‐110 (G>A). These results can be explained by a combination of historical–demographic characteristics together with evolutionary forces such as founder effect, genetic drift and probably selection by malaria. Knowledge of the mutational spectrum in the Balearic Islands will enable to optimize mutation detection strategy for genetic diagnosis of β‐thal in these islands.